2024 State of the Art Leadership Awards - Beth Myers; Clare Papay (Journal of Inclusive Postsecondary Education)
The Journal of Inclusive Postsecondary Education would like to recognize the following awardees for their contributions to the field. Each honoree received their award at the 2024 State of the Art Conference in Inclusive Postsecondary Education, held in Chapel Hill, North Carolina.